Analisis Kemandirian Belajar Siswa Ditinjau Dari Program Pembiasaan Pada Kurikulum Merdeka - Kumullah, Rahmah; Amrullah Mahmud (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to (1) analyze student learning independence; (2) analyze the implementation of the habituation program in instilling independent learning in the independent curriculum; and (3) know the factors that influence student learning independence. The research subjects were 28 students at SDN 180 Sikkojang. This research method uses descriptive qualitative research. Data collection techniques use observation, interviews, questionnaires, and documentation. The research results obtained were (1) related to indicators of learning independence, namely a) self-confidence, namely 63.1%; b) effectiveness in learning, namely 66.1%; c) discipline in learning, namely 68.7%, d) responsibility, namely 75.9%. (2) implementation of habituation programs in the independent curriculum, namely a) the habit of praying before and after learning; b) the habit of doing and submitting assignments on time; c) familiarization with Al-Quran literacy; d) literacy 30 minutes before the teaching and learning process; and e) the habit of compiling learning reflections through a daily journal. (3) learning independence is influenced by two factors, namely external and internal.